2024
DOI: 10.1162/jocn_a_02079
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmically Modulating Neural Entrainment during Exposure to Regularities Influences Statistical Learning

Laura J. Batterink,
Jerrica Mulgrew,
Aaron Gibbings

Abstract: The ability to discover regularities in the environment, such as syllable patterns in speech, is known as statistical learning. Previous studies have shown that statistical learning is accompanied by neural entrainment, in which neural activity temporally aligns with repeating patterns over time. However, it is unclear whether these rhythmic neural dynamics play a functional role in statistical learning or whether they largely reflect the downstream consequences of learning, such as the enhanced perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 117 publications
1
0
0
Order By: Relevance
“…This effect is commonly referred to as chunking (47). Our results accord well with a large number of studies that provided indirect evidence for chunking (20, 34, 48, 49, 4953) as well as few previous studies that directly reported neural representations to be chunked according to the predictive structure of a sensory sequence (26, 28). Our result extend these findings based on a temporally resolved RSA (29) which allowed us to track the representational dynamics throughout learning.…”
Section: Discussionsupporting
confidence: 91%
“…This effect is commonly referred to as chunking (47). Our results accord well with a large number of studies that provided indirect evidence for chunking (20, 34, 48, 49, 4953) as well as few previous studies that directly reported neural representations to be chunked according to the predictive structure of a sensory sequence (26, 28). Our result extend these findings based on a temporally resolved RSA (29) which allowed us to track the representational dynamics throughout learning.…”
Section: Discussionsupporting
confidence: 91%